Medicinal Vessels from Tell Atrib (Egypt) - Łajtar, Adam; Południkiewicz, Anna (Études et Travaux, 2017)
This article offers publication of seventeen miniature vessels discovered in Hellenistic strata of Athribis (modern Tell Atrib) during excavations carried out by Polish-Egyptian Mission in the 1980s/1990s. The vessels, made of clay, faience and bronze, are mostly imports from various areas within the Mediterranean, including Sicily and Lycia, and more rarely – local imitations of imported forms. Two vessels carry stamps with Greek inscriptions, indicating that they were containers for lykion, a medicine extracted from the plant of the same name, highly esteemed in antiquity. The vessels may be connected with a healing activity practised within the Hellenistic bath complex.